Vegetation concrete suitable for coastal protection and preparation method thereof

By using modified water repellent clay and slow-release composite fertilizer in planted concrete and adding reinforcing fibers, the problems of insufficient water resistance and low vegetation coverage of planted concrete substrates in tidal environments are solved, and higher durability and ecological restoration functions are achieved.

CN119841597APending Publication Date: 2025-04-18BEIBU GULF UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510044053.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the coastal tidal zone environment, existing phytogenetic concrete has problems such as insufficient matrix water resistance, poor moisture regulation ability, weak salt resistance, poor concrete durability and low vegetation coverage.

Method used

The frozen plant growth matrix with water repellent clay as the core is used to enhance the water resistance and structural stability of the matrix through surface modification technology, and combine slow-release composite fertilizers and reinforced fibers to improve the preparation process of concrete to improve its durability and ecological restoration function in tidal environments.

Benefits of technology

It significantly improves the durability and ecological restoration function of phytogenetic concrete in tidal environments, enhances the water resistance and vegetation coverage of the matrix, and extends the service life of the concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841597A_ABST
    Figure CN119841597A_ABST
Patent Text Reader

Abstract

The invention relates to the field of coast engineering and ecological restoration, and discloses vegetation concrete suitable for coast protection and a preparation method thereof.The concrete comprises cement, fine aggregate, coarse aggregate, a frozen plant growth matrix, water and an accelerator, and the matrix is composed of modified water-repellent clay, plant seeds, slow-release compound fertilizer, reinforced fibers and the like. The water resistance and the water retention capacity are remarkably improved through surface modification of the matrix, the slow-release compound fertilizer provides long-term nutrient support, and the matrix stability is improved through reinforced fibers; the interface bonding strength and the compression resistance of the concrete are optimized by adopting low-temperature mixing and an accelerator. The ecological protection system can adapt to the coastal tidal environment, and the ecological protection effects of high vegetation coverage rate and high durability are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coastal engineering and ecological restoration, and in particular to a vegetative concrete suitable for coastal protection and a preparation method thereof. Background Art

[0002] In coastal protection projects, vegetated concrete is an important material that combines ecological restoration and engineering protection functions. Existing vegetated concrete technology is mainly used in highway slopes, mine management and general slope protection. This type of vegetated concrete is usually composed of cement-based materials, aggregates and plant growth matrix, and its vegetation growth depends on plant seeds and nutrients in the matrix. However, traditional vegetated concrete shows obvious lack of adaptability when dealing with the special environment of the coastal tidal zone, and it is difficult to meet the long-term stability and ecological needs under complex hydrological conditions.

[0003] The coastal tidal zone environment is characterized by periodic immersion and drying. The erosion of salt water and the frequent wet-dry cycles put forward higher requirements on the structure of vegetated concrete and the growth of vegetation. However, the existing technology has the following shortcomings:

[0004] Insufficient water resistance of the substrate

[0005] In existing vegetation concrete, the plant growth matrix is ​​mostly made of ordinary soil or a mixture of soil and binder. This matrix is ​​prone to collapse and loss in the long-term immersion environment of the tidal zone, resulting in the inability to maintain the stability of the carrier required for plant growth. Especially in the low tide stage, due to the rapid loss of water in the matrix, the humidity of the plant growth environment cannot be maintained, which directly affects the growth and development of the plant root system. This matrix design is only suitable for stable slope protection projects, but shows obvious limitations in tidal dynamic environments.

[0006] Insufficient water regulation capacity of the substrate

[0007] Existing vegetated concrete technology does not fully consider the water retention capacity of the substrate in a dry environment. Ordinary soil substrates evaporate quickly at low tide, and the humidity drops too quickly, which is not conducive to the germination and growth of plant seeds. At the same time, when the water supply is insufficient, the substrate will become severely dry and cracked, further weakening its function as a carrier for plant growth. This phenomenon is particularly significant in tidal environments, posing a threat to the durability of vegetation coverage.

[0008] Saltwater intrusion stunts plant growth

[0009] The salt content of the coastal tidal zone environment is high. Ordinary soil substrates will absorb a large amount of salt during repeated immersion in salt water, making it difficult for plant seeds to germinate or inhibiting vegetation growth. In addition, salt accumulation will also aggravate the structural degradation of the substrate, significantly reducing the ecological function and engineering protection performance of the vegetated concrete.

[0010] Concrete durability issues

[0011] Traditional vegetation concrete is prone to cracking in tidal environments due to frequent wet-dry cycles and insufficient interface bonding strength. Especially when the hydration reaction is not effectively controlled during the mixing process, more pores will be generated in the concrete structure, reducing its compressive strength and resistance to salt erosion. Over time, these defects will lead to premature destruction of the concrete structure and affect the overall protection effect.

[0012] The vegetation coverage rate is low and the ecological restoration effect is limited

[0013] Traditional vegetated concrete has a low vegetation coverage rate in tidal environments. On the one hand, the lack of water and nutrients in the substrate leads to a low seed germination rate; on the other hand, the substrate is not strong enough and stable enough to provide effective support for plant roots. As a result, it is difficult for vegetated concrete to achieve long-term ecological restoration effects.

[0014] Therefore, the present invention proposes a vegetation concrete suitable for coastal protection and a preparation method thereof to solve the deficiencies of the prior art. Summary of the invention

[0015] The purpose of the present invention is to provide a vegetated concrete suitable for coastal protection and a preparation method thereof, so as to solve the problems of insufficient water resistance of the matrix, poor water regulation ability, weak salt resistance, poor concrete durability and low vegetation coverage in the tidal zone environment of the existing vegetated concrete. By improving the formula of the matrix and the preparation process of the concrete, the present invention can achieve higher durability and ecological restoration function in a complex tidal environment.

[0016] To achieve the above objectives, the present invention is implemented through the following technical solutions: a vegetation concrete suitable for coastal protection, the vegetation concrete comprises the following components, calculated by mass:

[0017] Cement: 40-45 parts;

[0018] Fine aggregate: 30-35 parts;

[0019] Coarse aggregate: 15-25 parts;

[0020] Frozen plant growth medium: 10-20 parts;

[0021] Ice-water mixture: 8-12 parts;

[0022] Accelerator: 1 to 3 parts;

[0023] Wherein, the frozen plant growth matrix is ​​made of the following components in parts by mass:

[0024] Water-repellent clay: 80-85 parts;

[0025] Surface modifier: 1.5-3 parts;

[0026] Plant seeds: 5-10 portions;

[0027] Plant seeds are used in the initial stage of vegetation growth, and salt-resistant plant seeds are selected, such as seashore paspalum or seashore thatch, to adapt to the coastal tidal environment.

[0028] Seeds obtain appropriate water and nutrient supply through the synergistic effect of the water retention capacity of the matrix and the slow-release fertilizer, thereby achieving rapid germination and growth.

[0029] Slow-release compound fertilizer: 8-12 parts;

[0030] Reinforcement fiber: 0.1-0.5 parts.

[0031] Preferably, the cement is high sulfate-resistant Portland cement.

[0032] Cement is the main cementing material of concrete, and its dosage directly affects the strength and durability of concrete. In the present invention, high sulfate-resistant silicate cement is preferably used to enhance the corrosion resistance of concrete in coastal tidal environments. High sulfate-resistant silicate cement can effectively resist the erosion of sulfates and chlorides in seawater and avoid the decrease of structural strength.

[0033] Cement generates hydration products (such as hydrated calcium silicate, calcium hydroxide, etc.) through hydration reaction in a humid environment. These products fill the pores of concrete and form a dense structure. The use of highly sulfate-resistant cement can reduce the expansive corrosion caused by sulfate ions and extend the service life of concrete.

[0034] Preferably, the fine aggregate is medium sand with a fineness modulus of 2.5 to 3.0.

[0035] The fine aggregate is medium sand with a fineness modulus of 2.5 to 3.0, which can effectively improve the compressive strength and construction performance of concrete. The particle size of medium sand is uniform, which can be closely combined with cement paste to reduce the segregation and bleeding of concrete mixture.

[0036] Fine aggregate fills the voids in concrete, making the overall structure denser, while forming a skeleton with cement paste to enhance overall strength and rigidity. In a tidal environment, good particle grading can reduce water penetration paths and improve the concrete's impermeability.

[0037] Preferably, the coarse aggregate is a continuously graded stone with a particle size of 5 to 10 mm.

[0038] Coarse aggregate is a continuously graded stone with a particle size of 5 to 10 mm, which has high strength and stability. Continuously graded stone can ensure that the internal void ratio of concrete is minimized, thereby improving its mechanical properties and durability.

[0039] Coarse aggregate acts as the skeleton material of concrete, providing compressive resistance and volume stability. Continuously graded aggregates can reduce the internal porosity of concrete during mixing, thereby reducing the rate of water intrusion in tidal environments.

[0040] Preferably, the accelerating setting agent is aluminum sulfate.

[0041] Preferably, the surface modifier in the frozen plant growth matrix is ​​octadecyl primary amine.

[0042] The water-repellent clay is treated with a surface modifier to form a hydrophobic surface. When the tide is high, the seawater soaks in and the seawater slowly infiltrates, which can provide water to the plants while maintaining the shape of the matrix. When the tide is low, the water will not evaporate quickly, leaving water for the plants to nourish.

[0043] Preferably, the slow-release compound fertilizer is modified urea.

[0044] The slow-release compound fertilizer is modified urea.

[0045] Preferably, the reinforcing fiber is polypropylene fiber.

[0046] The reinforcing fiber is polypropylene fiber, which is mainly used to enhance the toughness and crack resistance of the matrix.

[0047] Polypropylene fibers form a microscopic reinforcement effect by dispersing in the matrix, improving the tensile and crack resistance of the matrix and enhancing its overall stability in tidal environments.

[0048] Preferably, a method for preparing vegetation concrete suitable for coastal protection comprises the following steps:

[0049] S1. Weigh cement, fine aggregate and coarse aggregate in proportion and mix them for 30 to 60 seconds;

[0050] By premixing, the uniform distribution of cement and aggregate is ensured, creating conditions for the subsequent hydration reaction.

[0051] S2. Add ice-water mixture and accelerating agent and stir for 3 to 5 minutes;

[0052] In order to ensure that the frozen matrix does not melt quickly, the concrete can still maintain its original shape after mixing.

[0053] S3, adding frozen plant growth matrix in a matrix to stone mass ratio of 1:2 to 1:3, stirring for 2 to 4 minutes;

[0054] The matrix particles are uniformly mixed with the concrete, ensuring it provides a stable carrier for plant growth in a tidal environment.

[0055] S4, pouring the mixture into a mold, and demoulding after curing for 24 to 48 hours to complete the preparation.

[0056] Through wet curing, the concrete surface is kept moist to ensure that the hydration reaction proceeds fully.

[0057] Preferably, the preparation of the frozen plant growth substrate comprises the following steps:

[0058] (1) natural hydrophilic clay is air-dried and sieved, octadecyl primary amine is added and stirred evenly, and then heated at a constant temperature of 75° C. for 6 to 8 hours;

[0059] (2) leaving the obtained solution to stand for 2 to 3 hours;

[0060] (3) adding 15-20% water to the modified clay and stirring evenly, and mixing with plant seeds and slow-release compound fertilizer to form wet soil blocks with a particle size of 5-15 mm;

[0061] (4) After covering the outer layer with dry clay, freeze it at -10°C to -5°C for 4 to 6 hours to obtain a frozen plant growth medium.

[0062] The present invention provides a vegetation concrete suitable for coastal protection and a preparation method thereof. It has the following beneficial effects:

[0063] 1. The present invention adopts a plant growth matrix with water-repellent clay as the core, and significantly enhances the water resistance and structural stability of the matrix through surface modification technology, achieving the effect of adapting to the repeated immersion environment of the tidal zone. Compared with the solution in the prior art that does not perform hydrophobic treatment on the matrix, it solves the problem of easy loss of the matrix and reduced strength, and improves the service life and reliability.

[0064] 2. The present invention achieves the long-term release of nutrients in the matrix and the continuous optimization of the plant growth environment by evenly distributing the slow-release compound fertilizer and plant seeds in the modified clay and adopting the freezing molding process. Compared with the method of directly mixing into the soil or binder in the prior art, it avoids the shortcomings of fast nutrient loss and difficulty in long-term growth of plants, and ensures the growth and coverage effect of vegetation.

[0065] 3. The present invention adopts a concrete preparation process combining ice water mixing with an accelerator, controls the release of hydration heat and quickly forms a structurally stable concrete matrix, significantly improving the durability of concrete in tidal environments. Compared with the normal temperature mixing method in the prior art, it solves the problem of concrete cracking and failure in high humidity and high salt environments, ensuring the long-term stability of the project.

[0066] 4. The addition of reinforcing fibers in the present invention further enhances the crack resistance of the matrix and improves the adaptability and toughness of the overall material in the tidal zone. The prior art usually ignores the tensile strength and stability requirements of the matrix, resulting in the matrix being easily broken or damaged in a tidal environment, and the present invention successfully makes up for this defect. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 The present invention is a flow chart of the preparation method of vegetated concrete suitable for coastal protection. DETAILED DESCRIPTION

[0068] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0069] Please refer to the attached Figure 1 :

[0070] Embodiment 1:

[0071] Material ratio

[0072] By mass:

[0073] Cement: 42 parts;

[0074] Fine aggregate (medium sand with fineness modulus of 2.8): 32 parts;

[0075] Coarse aggregate (continuously graded stone with a particle size of 5 to 10 mm): 20 parts;

[0076] Frozen plant growth medium: 15 parts;

[0077] Ice water mixture: 10 parts;

[0078] Accelerator (aluminum sulfate): 2 parts.

[0079] Preparation of frozen plant growth medium

[0080] (1) Take natural hydrophilic clay, air-dry it to a moisture content of less than 5%, and pass it through a 2 mm sieve;

[0081] (2) adding 1.8% by weight of octadecyl primary amine and stirring thoroughly;

[0082] (3) heating at 75° C. for 6 hours, stirring every 2 hours, to form a preliminary modified clay;

[0083] (4) The obtained solution was allowed to stand for 3 hours to allow the surface to solidify;

[0084] (5) 15% water was evenly mixed into the modified clay, 8% slow-release compound fertilizer and 5% plant seeds (seashore paspalum) were added, and the mixture was manually kneaded into 10 mm granules;

[0085] (6) The surface of the particles is covered with dry clay powder to ensure that the matrix can still maintain its original shape after mixing;

[0086] (7) Freeze at -8°C for 4 hours to complete the matrix preparation.

[0087] Concrete preparation

[0088] (1) Weigh cement, fine aggregate and coarse aggregate in proportion and dry mix for 45 seconds;

[0089] (2) Add ice-water mixture (0°C) and add accelerating agent while stirring for 4 minutes;

[0090] (3) Mix the frozen plant growth medium with coarse aggregate in a mass ratio of 1:2 and stir at a low speed for 3 minutes;

[0091] (4) Pour the mixture into a mold and remove it from the mold after curing at room temperature for 24 hours.

[0092] Embodiment 2:

[0093] Material ratio

[0094] By mass:

[0095] Cement: 43 parts;

[0096] Fine aggregate (medium sand with fineness modulus of 2.6): 35 parts;

[0097] Coarse aggregate: 18 parts;

[0098] Frozen plant growth medium: 12 parts;

[0099] Ice-water mixture: 8 parts;

[0100] Accelerator: 3 parts.

[0101] Preparation of frozen plant growth medium

[0102] (1) Take hydrophilic clay, air-dry it to a moisture content of 3%, sieve it, add 2.0% octadecyl primary amine, and stir it evenly by hand;

[0103] (2) heating at 75°C for 8 hours, stirring every hour;

[0104] (3) The obtained solution was allowed to stand for 2 hours;

[0105] (4) The modified clay was mixed with 10% water, 10% slow-release compound fertilizer, and 8% plant seeds (seaside thatch) to prepare particles with a particle size of 5 mm;

[0106] (5) The surface is covered with a layer of dry modified clay and frozen for 6 hours (temperature is -10°C) to obtain a high water retention matrix.

[0107] Concrete preparation

[0108] (1) Mix cement and fine aggregate in proportion and dry mix for 30 seconds;

[0109] (2) Add ice-water mixture (temperature controlled at -2°C) and accelerating agent, and stir rapidly for 5 minutes;

[0110] (3) Add the frozen matrix and coarse aggregate into a mixer at a ratio of 1:2.5 and mix at low speed for 3 minutes;

[0111] (4) Pour into the mold, demould after curing for 48 hours, and transfer to wet curing for 28 days.

[0112] Embodiment 3:

[0113] Material ratio

[0114] By mass:

[0115] Cement: 45 parts;

[0116] Fine aggregate: 30 parts;

[0117] Coarse aggregate: 25 parts;

[0118] Frozen plant growth medium: 10 parts;

[0119] Ice-water mixture: 9 parts;

[0120] Accelerator: 2.5 parts.

[0121] Preparation of frozen plant growth medium

[0122] (1) Air-dried natural hydrophilic clay was sieved to a particle size of ≤2 mm;

[0123] (2) adding 1.5% of octadecyl primary amine modifier;

[0124] (3) heating at 75°C for 6 hours, stirring every hour;

[0125] (4) adding 15% water, 8% modified urea slow-release compound fertilizer, 5% plant seeds (Suaeda salsa) and 0.3% polypropylene fiber to prepare granules with a particle size of 15 mm;

[0126] (5) Freeze for 5 hours (-5°C) and cover the surface with a layer of dry clay powder.

[0127] Concrete preparation

[0128] (1) Dry mix cement, fine aggregate and coarse aggregate for 1 minute;

[0129] (2) Add ice-water mixture (0°C) and accelerating agent and stir for 3 minutes;

[0130] (3) Mix the matrix particles with the coarse aggregate in a mass ratio of 1:3 and stir slowly for 3 minutes;

[0131] (4) Pour into the mold, demould after initial curing for 24 hours, and then cure at room temperature for 14 days.

[0132] Comparative Example:

[0133] Comparative Example 1 (based on Example 1, without using a surface modifier)

[0134] Invention point comparison: The water-repellent clay was not surface-modified to verify the effect of the surface modifier on the water resistance and structural stability of the matrix.

[0135] Preparation process:

[0136] Matrix preparation:

[0137] (1) Take natural hydrophilic clay, air-dry it until the moisture content is less than 5%, and pass it through a 2 mm sieve;

[0138] (2) Surface modification with octadecyl primary amine;

[0139] (3) Mix 15% water, 8% slow-release compound fertilizer, and 5% plant seeds (seashore paspalum) and manually knead them into 10 mm wet soil blocks;

[0140] (4) The outer layer is covered with a layer of dry clay powder to ensure that the matrix can still maintain its original shape after mixing;

[0141] (5) Freeze the wet soil block at -8°C for 4 hours to obtain unmodified matrix particles.

[0142] Concrete preparation:

[0143] (1) Cement, fine aggregate and coarse aggregate were weighed according to the proportions in Example 1 and dry mixed for 45 seconds;

[0144] (2) Add ice-water mixture and accelerating agent and stir for 4 minutes;

[0145] (3) Mix the matrix particles and coarse aggregate in a ratio of 1:2 and stir at low speed for 3 minutes;

[0146] (4) After casting, the specimens were cured at room temperature for 24 hours and demolded to complete the preparation.

[0147] Comparative Example 2 (based on Example 2, without adding slow-release compound fertilizer)

[0148] Invention point comparison: No slow-release compound fertilizer was used to verify the effect of slow-release compound fertilizer on the long-term nutrient supply of plants.

[0149] Preparation process:

[0150] Matrix preparation:

[0151] (1) Take natural hydrophilic clay, air-dry it to a moisture content of 3%, sieve it, add 1.8% octadecyl primary amine, and stir evenly;

[0152] (2) Heating at 75°C for 6 hours, stirring every hour;

[0153] (3) leaving the obtained solution to stand for 3 hours;

[0154] (4) No slow-release compound fertilizer was added, only 10% of plant seeds (seaside thatch) and 15% of water were added to make particles with a particle size of 5 mm;

[0155] (5) Freeze for 6 hours (-10°C) to obtain substrate particles without added slow-release fertilizer.

[0156] Concrete preparation:

[0157] According to the process of Example 2, the matrix of Comparative Example 2 is used to replace the matrix in Example 2, and the other steps remain the same to complete the preparation of the concrete specimen.

[0158] Comparative Example 3 (based on Example 3, without using an accelerating agent)

[0159] Invention point comparison: No accelerating setting agent was added to verify the effect of accelerating setting agent on the early strength of concrete and construction efficiency.

[0160] Preparation process:

[0161] Matrix preparation:

[0162] The matrix was prepared according to the process of Example 3, with the addition of modified water-repellent clay, slow-release compound fertilizer and polypropylene fiber, and the specific parameters remained the same.

[0163] Concrete preparation:

[0164] (1) Weigh cement, fine aggregate and coarse aggregate according to the proportions in Example 3;

[0165] (2) Using room temperature water (20°C) instead of ice water mixture, without adding accelerator;

[0166] (3) After stirring for 3 minutes, add the matrix particles and mix at low speed for 3 minutes;

[0167] (4) After casting, the specimens were cured at room temperature for 48 hours and demolded to complete the specimen preparation.

[0168] Comparative Example 4 (based on Example 1, modified water-repellent clay was not used, and ordinary soil was used instead)

[0169] Invention point comparison: Ordinary soil replaces modified water-repellent clay to verify the role of water-repellent clay in structural stability and water retention capacity in a tidal environment.

[0170] Preparation process:

[0171] Matrix preparation:

[0172] (1) Use ordinary soil (untreated), air-dry to 5% moisture content, and sieve to 2 mm;

[0173] (2) No surface modifiers were added;

[0174] (3) Mix 15% water, 8% slow-release compound fertilizer, and 5% plant seeds (seashore paspalum) and manually knead them into 10 mm wet soil blocks;

[0175] (4) The outer layer is covered with ordinary soil powder and frozen for 4 hours (-8°C) to obtain matrix particles.

[0176] Concrete preparation:

[0177] Concrete was prepared according to the process of Example 1, using the matrix of Comparative Example 4 to replace the matrix in Example 1, and the other steps remained the same.

[0178] Comparative Example 5 (based on Example 2, without adding reinforcing fiber)

[0179] Inventive point comparison: No polypropylene fiber was added to verify the effect of the reinforcing fiber on the crack resistance of the matrix.

[0180] Preparation process:

[0181] Matrix preparation:

[0182] (1) Taking natural hydrophilic clay, surface modification (octadecyl primary amine) was performed according to the method of Example 2;

[0183] (2) adding 15% water, 10% slow-release compound fertilizer, and 8% plant seeds (seaside thatch), but without adding polypropylene fiber;

[0184] (3) After kneading into 5 mm pellets, the pellets were frozen for 6 hours (-10°C) to obtain matrix pellets without reinforcing fibers added.

[0185] Concrete preparation:

[0186] Concrete was prepared according to the process of Example 2, using the matrix of Comparative Example 5, and the other steps remained the same.

[0187] Test experiment:

[0188] Experiment 1: Comparative experiment on water resistance and loss rate of substrate

[0189] Experimental Description

[0190] Purpose

[0191] The water resistance and anti-loss performance of the modified water-repellent clay matrix of the present invention in a tidal environment were verified, and the effect of surface modification on the stability of the matrix was analyzed.

[0192] Experimental Materials

[0193] Example 1 Matrix: Modified water-repellent clay (octadecyl primary amine) is used;

[0194] Comparative Example 1: Matrix: hydrophilic clay was used directly without surface modification;

[0195] Saline (3.5% NaCl solution), room temperature 25°C.

[0196] Experimental procedures

[0197] Matrix preparation

[0198] The matrix particles of Example 1 and Comparative Example 1 were weighed separately, 50 g each, with a diameter of 10 mm.

[0199] The substrate was placed in two groups of test containers with good water permeability, which were marked as Group A (Example 1) and Group B (Comparative Example 1).

[0200] Tidal environment simulation

[0201] Two groups of substrate particles were placed in a tidal circulation apparatus and subjected to a daily soaking-drying cycle;

[0202] The matrix particles were soaked in saline for 6 h each time and then dried in a constant temperature and humidity chamber at 25°C and 50% humidity for 6 h;

[0203] At the end of every two days, each group of substrate was taken out and weighed, and the remaining substrate mass was recorded.

[0204] Experimental cycle

[0205] The entire experiment lasted 14 days, with a total of 7 complete tidal cycles.

[0206] Churn rate calculation formula

[0207] Loss rate (%) = [(initial mass - remaining mass) / initial mass] × 100%.

[0208] Experimental data:

[0209] Table 1: Comparative experimental data of matrix water resistance and loss rate

[0210]

[0211] The surface modification obviously changes the water contact angle of the clay particles, making them more hydrophobic. The core of this change is the hydrophobic film formed after the reaction of octadecyl primary amine, which reduces the infiltration of water. At high tide, the seawater is soaked, and the slow infiltration of seawater can supply water to plants while maintaining the shape of the matrix. At low tide, the water will not evaporate quickly, but will be left for the plants to nourish. In Comparative Example 1, which has not been modified, the salt water penetrates quickly, destroying the matrix structure, and the particles are loose and seriously lost during tidal scouring. This also directly verifies the stability of water-repellent clay in a tidal environment.

[0212] After tidal cycles, the matrix particle loss rate of Example 1 is only about half of that of Comparative Example 1. This significant difference reflects the reduction of surface energy in the Laplace-Young equation, which reduces the interfacial bonding ability between the matrix and water. In Comparative Example 1, the hydrophilic clay has high surface energy, and water quickly invades, causing the particles to swell and break. In the repeated changes of soaking-drying, it is difficult for the unmodified matrix to maintain the particle shape.

[0213] Furthermore, water-repellent modification is not just a surface change, but also enhances the physical structural integrity of the matrix to a certain extent. The outside of the matrix particles is protected by a hydrophobic layer, and the particle shape remains relatively good after tidal cycles. In Comparative Example 1, due to the destruction of the structure, the particles disintegrated, and eventually showed a significant decrease in quality. This comparison directly reflects the advantages of surface modification in environmental adaptability.

[0214] Experiment 2: Comparative experiment on water retention performance of substrate

[0215] Experimental Description

[0216] Purpose

[0217] The effect of the addition of the slow-release compound fertilizer on the water-retaining performance of the matrix particles was verified, and the water-retaining capacity of the modified matrix in a low-tide environment was analyzed.

[0218] Experimental Materials

[0219] Example 2 Matrix: modified water-repellent clay is used, and slow-release compound fertilizer (modified urea) is added.

[0220] Comparative Example 2 Matrix: No slow-release compound fertilizer was added, and other components were consistent with Example 2.

[0221] Room temperature water, constant temperature and humidity laboratory.

[0222] Experimental procedures

[0223] Matrix preparation

[0224] The matrix particles of Example 2 and Comparative Example 2 were weighed separately, 50 g each, and the particle diameter was 10 mm.

[0225] The two groups of substrates were labeled as Group A (Example 2) and Group B (Comparative Example 2), respectively.

[0226] Saturated water treatment

[0227] The two groups of substrates were completely immersed in clean water for 3 hours to ensure that the substrate particles reached the water saturation state.

[0228] After soaking, take out the matrix, absorb the surface moisture with filter paper, and record the initial saturated mass.

[0229] Water retention performance test

[0230] The two groups of substrates were placed in a constant temperature and humidity chamber (temperature 25°C, humidity 50%);

[0231] Weigh the substrate mass every hour and record the residual water at each moment;

[0232] The test was continued for 10 hours until the substrate was completely dehydrated.

[0233] Water retention rate calculation formula

[0234] Water retention rate (%) = [(initial saturated mass - current mass) / initial saturated mass] x 100%.

[0235] Experimental data

[0236] Table 2: Comparative experimental data of matrix water retention performance

[0237]

[0238] The addition of slow-release compound fertilizer is obviously not only a supply of nutrients, but also an important factor affecting the water retention capacity of the matrix. As time goes by, the rate of water evaporation is significantly lower than that of Comparative Example 2. This shows that the slow-release compound fertilizer not only provides nutrient support for plant growth, but also delays the drying process of the matrix through moisture regulation. This feature is particularly important in low-tide environments and can maintain the appropriate humidity of the matrix.

[0239] In Comparative Example 2, where no slow-release compound fertilizer was added, the water loss rate of the matrix particles was significantly accelerated. Due to the single hydrophobic effect of the surface-modified clay and the lack of internal moisture regulation ability, the particles quickly dehumidified in a dry environment. In particular, after the experiment was carried out for 4 hours, the moisture content of the matrix particles decreased sharply. This also reflects that the water absorption and slow-release properties of the compound fertilizer are the key to prolonging the wetting time of the matrix.

[0240] From a mechanistic point of view, the water-absorbing film layer formed by the coating material of the slow-release compound fertilizer plays an important role in water balance. When the humidity of the surrounding environment decreases, the water release rate in the film layer is slow, maintaining the moist state inside the matrix. In Comparative Example 2, lacking the protection of this layer of water-absorbing material, the matrix cannot maintain humidity for a long time by relying on the surface hydrophobic properties, and ultimately causes the water retention rate to be much lower than that of Example 2. This also directly verifies the necessity of slow-release compound fertilizer in the design of tidal environment matrix.

[0241] Experiment 3: Concrete compressive strength comparison experiment

[0242] Experimental Description

[0243] Purpose

[0244] Verify the effect of the addition of accelerator on the compressive strength of bioreinforced concrete, and analyze the role of accelerator in enhancing the early strength and overall stability of concrete.

[0245] Experimental Materials

[0246] Example 3 Concrete: Using an accelerating agent (aluminum sulfate), prepared according to the formula of Example 3;

[0247] Comparative Example 3 concrete: no accelerating agent was added, and other formulas were consistent with those of Example 3;

[0248] Concrete test mould (size 100 mm x 100 mm x 100 mm);

[0249] Compression testing machine.

[0250] Experimental procedures

[0251] Concrete preparation

[0252] Concrete mixtures of Example 3 and Comparative Example 3 were prepared according to the proportions;

[0253] In Example 3, an accelerating setting agent (aluminum sulfate, 2.5%) was added; in Comparative Example 3, no accelerating setting agent was used, and the other steps remained the same;

[0254] After the concrete is mixed, pour it into the mold immediately and vibrate until all bubbles are expelled.

[0255] Maintenance process

[0256] The cast specimens were placed in a wet curing room with a humidity of 95% and a temperature of 20°C ± 2°C;

[0257] After the initial curing for 24 hours, demoulding is carried out and wet curing is continued for up to 28 days.

[0258] Compressive strength test

[0259] After 28 days of curing, take out the specimens and wipe them clean;

[0260] Use a pressure testing machine to load at a speed of 0.5 MPa / s until the specimen fails, and record the maximum failure load;

[0261] The compressive strength is calculated according to the following formula:

[0262] Compressive strength (MPa) = breaking load (N) / specimen pressure bearing area (mm 2 ).

[0263] Experimental Replication

[0264] Three specimens were set in each group, and the average value was taken as the test result.

[0265] Experimental data:

[0266] Table 3: Comparative experimental data of concrete compressive strength

[0267] Test piece number Example 3 Compressive Strength (MPa) Comparative Example 3 Compressive Strength (MPa) 1 44.3 38.9 2 46.2 37.5 3 43.7 39.8 average value 44.7 38.7

[0268] The addition of the accelerator significantly improves the early hydration process of concrete, especially under the action of aluminum sulfate, accelerating the initial reaction on the surface of cement particles. It can be observed through experiments that the compressive strength of Example 3 is much higher than that of Comparative Example 3 without the addition of the accelerator. The accelerator guides the rapid generation of the hydration reaction, so that the initial hydration products such as calcium aluminate can quickly fill the pores and form a denser microstructure. In Comparative Example 3, the hydration rate is slow, and the pores are not fully filled in the early stage, resulting in insufficient internal structural strength of the specimen.

[0269] From a mechanistic point of view, the presence of the accelerator optimizes the hydration reaction rate, but more importantly, it changes the morphological distribution of the hydration products to a certain extent. The microscopic observation results of the specimens show that the calcium silicate hydrate formed under the guidance of the accelerator presents a relatively uniform network structure, which has a very obvious effect on the sealing of pores. In contrast, due to the lack of accelerator in Comparative Example 3, the hydration reaction between cement particles is slow, the generated gel is unevenly distributed, the porosity is higher, and the structure is loose, which ultimately leads to a decrease in compressive strength.

[0270] In addition, the use of accelerators also reduces the risk of early cracking of concrete to a certain extent. Comparative Example 3 has obvious shrinkage cracks during the curing stage, while the specimens of Example 3 show better integrity. Combined with the data and phenomena of this experiment, the improvement of concrete performance by accelerators is not only reflected in mechanical strength, but also in structural uniformity and porosity optimization. This is also one of the core advantages of the present invention in ensuring the stability of concrete under tidal conditions.

[0271] Experiment 4: Vegetation coverage comparison experiment

[0272] Experimental Description

[0273] Purpose

[0274] The effect of the modified water-repellent clay in the present invention on improving the vegetation coverage of vegetated concrete was verified, and the role of the modified matrix in providing a stable plant growth environment was analyzed.

[0275] Experimental Materials

[0276] Example 1 Matrix: Matrix prepared by modified water-repellent clay (octadecyl primary amine);

[0277] Comparative Example 4: substrate prepared from unmodified common soil;

[0278] Plant seeds (Seashore Paspalum);

[0279] Concrete specimen mold (size 100 mm × 100 mm × 100 mm);

[0280] Saline (3.5% NaCl solution).

[0281] Experimental procedures

[0282] Matrix and specimen preparation

[0283] Prepare the matrix of Example 1 and the matrix of Comparative Example 4, 50 g each;

[0284] A 10 mm thick matrix layer was evenly laid on the surface of the 100 mm × 100 mm × 100 mm concrete specimen;

[0285] There are 5 test pieces in each group, Example 1 is marked as Group A, and Comparative Example 4 is marked as Group B.

[0286] Sowing seeds

[0287] Evenly spread plant seeds (2 g / test piece) on the substrate surface and cover the seeds with a small amount of substrate to a thickness of about 3 mm;

[0288] Each specimen was sprayed with water (salt water) evenly until the substrate surface was completely wetted.

[0289] Tidal environment simulation

[0290] The specimens were placed in a tidal simulation device and subjected to daily immersion-drying cycles;

[0291] Soak in salt water for 6 hours, dry for 6 hours, and the cycle lasts for 14 days;

[0292] Spray water regularly every day to keep the substrate moist, and do not water additionally during the dry phase.

[0293] Vegetation coverage determination

[0294] After the test, the specimen surface was covered with a transparent grid (grid size 1 cm × 1 cm), and the proportion of plant coverage in the grid was recorded;

[0295] Vegetation coverage rate (%) = (number of covered grids / total number of grids) × 100%.

[0296] Experimental data:

[0297] Table 4: Vegetation coverage comparison experimental data

[0298] Test piece number Example 1 Vegetation coverage (%) Comparative Example 4 Vegetation Coverage (%) 1 87.5 63.4 2 85.9 60.2 3 88.4 65.3 4 86.7 62.8 5 84.3 59.5 average value 86.6 62.2

[0299] The application of modified water-repellent clay enables the substrate to maintain a more stable structure in a tidal environment. The significant increase in vegetation coverage is attributed to the superior performance of the modified substrate. When the tide is high, the seawater soaks in and the seawater slowly infiltrates, which can provide water to the plants while maintaining the shape of the substrate. When the tide is low, the water will not evaporate quickly, leaving water for the plants to nourish.

[0300] Experiment 5: Concrete crack resistance performance comparison experiment

[0301] Experimental Description

[0302] Purpose

[0303] The effect of reinforcing fibers on the crack resistance of bioreinforced concrete was verified, and its effect on the tensile strength and crack control of concrete under tidal conditions was evaluated.

[0304] Experimental Materials

[0305] Example 2 Concrete: Containing polypropylene fiber (0.3%), prepared according to the formula of Example 2;

[0306] Comparative Example 5 Concrete: No polypropylene fiber was added, and the remaining components and preparation process were the same as those of Example 2;

[0307] Concrete sheet mold (300 mm × 300 mm × 50 mm);

[0308] Single point loading testing machine.

[0309] Experimental procedures

[0310] Concrete preparation

[0311] Concrete of Example 2 and Comparative Example 5 were prepared respectively;

[0312] In Example 2, 0.3% polypropylene fiber (by mass) was added in proportion and evenly dispersed; in Comparative Example 5, no reinforcing fiber was added;

[0313] Pour two batches of concrete into the slab mould and vibrate to remove air.

[0314] Maintenance process

[0315] The cast thin plate specimens were cured in a wet curing room with a humidity of 95% and a temperature of 20°C ± 2°C for 28 days;

[0316] Ensure that there is no external force affecting the surface of the specimen during curing.

[0317] Crack resistance test

[0318] Place the specimen on a single-point loading testing machine;

[0319] Apply a load at the center of the thin plate at a loading speed of 0.1 kN / s, and record the load value when the crack first appears (record when the crack width is ≥ 0.1 mm);

[0320] Three specimens were tested in each group and the average value was taken.

[0321] Experimental Replication

[0322] Three specimens were set in each group, and the test results were averaged.

[0323] Experimental data:

[0324] Table 5: Comparative experimental data of concrete crack resistance

[0325] Test piece number Example 2 First crack load (kN) Comparative Example 5 First Crack Load (kN) 1 5.2 3.9 2 4.8 4.1 3 5.1 3.7 average value 5.0 3.9

[0326] The addition of polypropylene fibers obviously forms an effective anti-crack "skeleton" inside the thin slab concrete. From the test results, the first crack appeared when the load reached 5.0kN in Example 2, while cracks appeared in Comparative Example 5 when the load reached 3.9kN. This difference is mainly attributed to the role of reinforcing fibers in stress dispersion. The fiber network is evenly distributed in the concrete, providing additional tensile strength while effectively delaying the formation and expansion of cracks. Comparative Example 5 lacks fiber support, and internal stress is concentrated in weak areas, resulting in earlier cracks.

[0327] The improvement of crack resistance not only depends on the distribution of fibers, but also reflects the optimization of the internal structure of the matrix by fibers. In a tidal environment, concrete generates internal stress due to repeated immersion and drying. Polypropylene fibers can absorb part of the internal stress through their flexibility and tensile strength, thereby slowing down the rate of crack generation. However, due to the lack of fiber tensile effect, the cracks in Comparative Example 5 expand rapidly, showing an obvious deterioration trend, which is also a common cause of failure of ordinary concrete in a tidal environment.

[0328] Mechanistically, the role of fiber is not only mechanical reinforcement, but also forms a microscopic "reinforcement" effect in the concrete matrix. The fiber has a good interface with the cement paste, which can lock micro cracks and prevent them from expanding into through cracks. Compared with the phenomenon of rapid penetration of cracks in Comparative Example 5, the cracks in the thin plate of Example 2 are only partially superficial, which also shows that the addition of fiber plays a positive role in crack control, providing higher reliability and service life for vegetation concrete in tidal environments.

[0329] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A vegetative concrete suitable for coastal protection, characterized in that: The vegetation concrete comprises the following components, calculated by weight: Cement: 40-45 parts; Fine aggregate: 30-35 parts; Coarse aggregate: 15-25 parts; Frozen plant growth medium: 10-20 parts; Ice-water mixture: 8-12 parts; Accelerator: 1 to 3 parts; Wherein, the frozen plant growth matrix is ​​made of the following components in parts by mass: Water-repellent clay: 80-85 parts; Surface modifier: 1.5-3 parts; Plant seeds: 5-10 portions; Slow-release compound fertilizer: 8-12 parts; Reinforcement fiber: 0.1-0.5 parts.

2. The vegetated concrete suitable for coastal protection according to claim 1, characterized in that: The cement is high sulfate-resistant Portland cement.

3. The vegetated concrete suitable for coastal protection according to claim 1, characterized in that: The fine aggregate is medium sand with a fineness modulus of 2.5 to 3.

0.

4. The vegetated concrete suitable for coastal protection according to claim 1, characterized in that: The coarse aggregate is a continuously graded stone material with a particle size of 5 to 10 mm.

5. The vegetative concrete suitable for coastal protection according to claim 1, characterized in that: The accelerating setting agent is aluminum sulfate.

6. The vegetated concrete suitable for coastal protection according to claim 1, characterized in that: The surface modifier in the frozen plant growth matrix is ​​octadecyl primary amine.

7. The vegetated concrete suitable for coastal protection according to claim 1, characterized in that: The slow-release compound fertilizer is modified urea.

8. The vegetative concrete suitable for coastal protection according to claim 1, characterized in that: The reinforcing fiber is polypropylene fiber.

9. A method for preparing a vegetation concrete suitable for coastal protection according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Weigh cement, fine aggregate and coarse aggregate in proportion and mix them for 30 to 60 seconds; S2. Add ice-water mixture and accelerating agent and stir for 3 to 5 minutes; S3, adding frozen plant growth matrix in a matrix to stone mass ratio of 1:2 to 1:3, stirring for 2 to 4 minutes; S4, pouring the mixture into a mold, and demoulding after curing for 24 to 48 hours to complete the preparation.

10. The method for preparing the vegetation concrete suitable for coastal protection according to claim 9, characterized in that: The preparation of the frozen plant growth matrix comprises the following steps: (1) natural hydrophilic clay is air-dried and sieved, octadecyl primary amine is added and stirred evenly, and then heated at a constant temperature of 75° C. for 6 to 8 hours; (2) leaving the obtained solution to stand for 2 to 3 hours; (3) adding 15-20% water to the modified clay and stirring evenly, and mixing with plant seeds and slow-release compound fertilizer to form wet soil blocks with a particle size of 5-15 mm; (4) After covering the outer layer with dry clay, freeze it at -10°C to -5°C for 4 to 6 hours to obtain a frozen plant growth medium.

Citation Information

Cited By

  • High and steep slope strong freezing and thawing resistant vegetation block and green low-temperature freezing preparation method and application

    CN121970568A